Prospective evaluation of mpMRI-derived nomograms for detecting prostate cancer in PI-RADS v2.1 upgraded and non-upgraded lesions - Yi, Ying; Wang, Hang; Cheng, Dongliang; Xu, Zhifeng; Zhang, Xianhai; Luo, Chun; Zhao, Hai (Frontiers in Oncology, 2025)
BackgroundLimited data exist on the performance of Prostate Imaging Reporting and Data System (PI-RADS) v2.1 upgraded and non-upgraded lesions, both alone and in combined with multiparametric MRI (mpMRI) features, for prostate cancer detection.ObjectiveTo evaluate the rates of prostate cancer (PCa) and clinically significant prostate cancer(csPCa) rates in PI-RADS v2.1 upgraded and non-upgraded lesions, and to identify mpMRI features that improve detection accuracy.MethodsThis study included men who underwent mpMRI and ultrasound-guided (US-guided) biopsy from March 2023 to April 2024. MRI scans were prospectively evaluated according to PI-RADS v2.1. MpMRI features were extracted from lesion contours, including three-dimensional maximum diameter, lesion volume, sphericity, surface-to-volume ratio (SVR), T2-weighted imaging signal intensity(T2WI SI), diffusion-weighted imaging(DWI) SI, T1, T2, proton density (PD), apparent diffusion coefficient (ADC), and dynamic contrast-enhanced (DCE) MRI-derived time intensity curve (TIC). Univariable and multivariable logistic regression analyses were performed to identify features associated with PCa and csPCa in different prostate zones (transition zone and peripheral zone).ResultsA total of 94 patients(mean age, 65.7 years) with 234 lesions were included. Significant differences were observed between upgraded and non-upgraded PI-RADS 4 lesions(p < 0.05) in the peripheral zone (PZ), whereas no significant differences were found in the transition zone (TZ). Risk factors for csPCa in the TZ included lesion diameter, TIC type III, capsule, T1 and PD values. For csPCa in the PZ, T1, SVR, DWI SI, and ADC values were identified as important risk factors. ROC analysis demonstrated high diagnostic accuracy for csPCa detection, with AUCs of 0.93 (TZ) and 0.96 (PZ).ConclusionPI-RADS v2.1 upgrading rules improve cancer detection in the TZ, but upgrading PI-RADS category 3 lesions in the PZ may lead to unnecessary biopsies. MpMRI-based nomograms enhance predictive accuracy for both PCa and csPCa.